Protocol for measuring protein synthesis in specific cell types in the mouse brain using in vivo non-canonical amino acid tagging - Mehdi Hooshmandi; Calvin Wong; Kevin C. Lister; Nicole Brown; Weihua Cai; David Ho-Tieng; Patricia Stecum; Thomas Backman; Elie Kostantin; Arkady Khoutorsky (STAR Protocols, 2024)
Summary: The fluorescent non-canonical amino acid tagging (FUNCAT) technique has been used to visualize newly synthesized proteins in cell lines and tissues. Here, we present a protocol for measuring protein synthesis in specific cell types in the mouse brain using in vivo FUNCAT. We describe steps for metabolically labeling newly synthesized proteins with azidohomoalanine, which introduces an azide group into the polypeptide. We then detail procedures for binding a fluorophore-conjugated alkyne to the azide group to allow its visualization.For complete details on the use and execution of this protocol, please refer to tom Dieck et al. (2012)1 and Hooshmandi et al. (2023).2 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.